SCHOOL DROPOUT RATE IN THE SHADOW OF ECONOMIC CRISIS - Dede Gustian; Deisye Supit; Arnadi (CV. ADIBA AISHA AMIRA, 2024)
The economic crisis has had a significant impact on various sectors of life, including education. One of the problems that emerged was the drastic increase in dropout rates among children from underprivileged families. The economic impact leads to the inability of families to fulfil basic needs, including the cost of their children's education. As a result, many students have to leave school to help the family economy or because parents lose their jobs and income. To address this problem, a comprehensive solution involving various parties is needed. Financial support in the form of education subsidies can help ease the burden of school fees. In addition, improving the quality and access to better education facilities will provide fairer learning opportunities for all students. The implementation of technology in education is also an important step to ensure flexible access to learning, especially for those who are physically challenged to attend school. Collaboration between the government, educational institutions, NGOs and communities is crucial in creating an enabling environment for children to continue their education amidst the economic crisis. With concerted efforts, it is hoped that the dropout rate can be reduced and children can continue to get proper educational opportunities